Visual Cryptographic Authentication for Online Payment System - Vinod, LB; Nithyanada, CR (International Journal of Computer Sciences and Engineering, 2025)
In these days many people are using e-commerce market for online shopping like example: Flip kart, Amazon and etc. With huge demand in-shopping or increasing popularity of online shopping security issues of debit, credit and personnel information has been raised. This project presents a new approach for providing restricted or limited information that’s only necessary for fund transfer during online transaction with this we are reducing the entering detailed information of customer like card number, CVV and etc. And this project or approach uses combined application of LSB based steganography and visual cryptography. In this project first we encrypt the user or customer credentials in an image by using LSB Steganography process and then we use visual cryptography to divide an image into two shares. Reverse visual cryptography is applied to get an original image and data is retrieved from image and sent to the bank for verification of legitimate user if user is valid the fund will be transferred to the merchant. A quick development in E-Commerce business sector is seen in late time all through the world. With steadily expanding prominence of internet shopping, Debit or Credit card misrepresentation and individual data security are significant attentiveness toward clients, dealers and banks particularly on account of CNP (Card Not Present). This paper displays another methodology for giving restricted data just that is vital for store exchange amid web shopping subsequently defending client information and expanding client certainty and forestalling wholesale fraud. The system uses joined utilization of steganography and visual cryptography for this reason.